1989
DOI: 10.1038/clpt.1989.53
|View full text |Cite
|
Sign up to set email alerts
|

The effect of probenecid on the renal elimination of cimetidine

Abstract: It is generally assumed that the systems involved in the transport of organic cations and organic anions in the renal proximal tubule are substrate selective (i.e., organic anions do not inhibit organic cation transport and vice versa). However, recent data obtained in vitro have suggested that the organic anion probenecid inhibits the renal transport of the organic cation cimetidine. We addressed the question of whether this interaction is biologically relevant in human beings. The study involved a two-treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
32
0

Year Published

1991
1991
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 0 publications
5
32
0
Order By: Relevance
“…This finding is difficult to explain, although two mechanisms are possible-a reduction of the glomerular filtration rate (GFR) by probenecid or an inhibition of the secretory component of creatinine elimination. It has been reported (Gisclon et al, 1989) that probenecid decreases GFR (inulin clearance) in man by 29%. This decrease in GFR is comparable with the extent of impairment of creatinine clearance found in our study, as well as with the results reported in two other studies in humans where probenecid reduced inulin clearance by 22% and 27% (Odlind et al, 1983a,b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is difficult to explain, although two mechanisms are possible-a reduction of the glomerular filtration rate (GFR) by probenecid or an inhibition of the secretory component of creatinine elimination. It has been reported (Gisclon et al, 1989) that probenecid decreases GFR (inulin clearance) in man by 29%. This decrease in GFR is comparable with the extent of impairment of creatinine clearance found in our study, as well as with the results reported in two other studies in humans where probenecid reduced inulin clearance by 22% and 27% (Odlind et al, 1983a,b).…”
Section: Discussionmentioning
confidence: 99%
“…Probenecid is reported to have a modest inhibitory effect in vitro on the uptake of another glycoside, ouabain, in rat liver slices (Erttmann & Damm, 1974) and in rat isolated hepatocytes (Eaton & Klaassen, 1978) as well as being able to lower the renal clearance of cimetidine in healthy volunteers (Gisclon et al, 1989). Hence, the question arises whether an anion like probenecid may affect secretion and thus the kinetics of digoxin in man.…”
Section: Introductionmentioning
confidence: 99%
“…Organic anion transporters (OAT) and organic cation transporters (OCT) are involved in active renal secretion of numerous drug molecules [5] and have been found also at various other sites in the body. Probenecid has been reported to interact with both [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…Blood samples were taken before the start of the ciprofloxacin infusion, 10 and 20 min after the start of infusion, at the end of infusion, and 5, 10, 20, 30, 45, 60 and 90 min and 2, 3,4,5,6,8,10,12,16,24,30,36 and 48 h after the end of the infusion. The samples were centrifuged immediately.…”
Section: Sampling Schedulementioning
confidence: 99%
See 1 more Smart Citation